The Covid Pandemic Testing the Resilience of the United States, China and Indonesia Capital Markets - Achmad Agus Priyono; Ety Saraswati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
There are two main factors that influence the rise and fall of the index, namely internal factors and external factors. The external factor currently experiencing volatility in the stock market is the coronavirus outbreak. Where the presence of the Coronavirus on this earth has caused panic in various parts of the world. The epidemic attacks various levels of society, especially for those who have congenital diseases. This study aims to analyze the resilience of the capital markets in the United States, China and Indonesia in the 60 days before and after the positive confirmation of COVID-19 in each country. The variable of capital market resilience in the United States is used as a proxy for the DJI index, while the resilience of the capital market in China is used as a proxy for the SSEC index, while the resilience of the capital market in Indonesia is used as a proxy for the IDX index. The paper tries to determine whether there are differences in the resilience of the capital market before and before the covid outbreak in the American, Chinese and Indonesian capital markets. The results of the study prove that the Covid outbreak has had a very bad impact on the stock markets of Indonesia and the United States. The tool on the test used to prove that there is a difference in resilience in the capital markets in Indonesia and the United States in the 60 days before and after being confirmed positive for Covid. Meanwhile, in the capital market in China, it was found that there was no difference in the resilience of the capital market in the 60 days before and before being confirmed positive for Covid. This condition proves the country's success in handling and controlling the covid outbreak.